Electrocatalytic hydrogen evolution under neutral pH conditions: current understandings, recent advances, and future prospects - Zhou, Zheng; Pei, Zengxia; Wei, Li; Zhao, Shenlong; Jian, Xian; Chen, Yuan (Energy & environmental science, 2020)
Hydrogen production from direct water electrolysis has long been pursued as a key that may revolutionize the hydrogen economy. With the rapid availability of electricity generated using renewable energy resources, this long-pursued target is now closer to reality than ever before. To date, most studies regarding electrocatalytic hydrogen evolution reaction (HER) are carried out in strong acidic/alkali electrolytes. However, hydrogen production from HER under extreme pH conditions has several drawbacks, including a corrosive working environment, the requirement of expensive anion/cation exchange membranes, and acidic/alkali withstanding electrocatalysts. The more sustainable approach to address these drawbacks is to deploy neutral/near-neutral electrolytes for HER. Regretfully, both theoretical discussions and practical applications regarding HER under neutral/near-neutral conditions are relatively rare and very elusive. In this review, we systematically discuss the current understandings of HER mechanisms under neutral conditions and analyze the influences of different types of neutral electrolytes. The most recent advances in the development of neutral HER electrocatalysts are summarized and exemplified, and general electrocatalyst design principles are highlighted. Lastly, we provide our perspective on the potential future research direction. We hope that this review inspires future endeavors to realize efficient HER for hydrogen production under neutral conditions. This review summarizes the latest advances in hydrogen evolution reaction under neutral conditions to enlighten future researches.